Implementation of the Masaco Filter Innovation (Water Hyacinth Cellulose Membrane) as a Solution for Wastewater Management at Pertamina FT Cikampek and Clean Water Availability in Walahar Village - Taufik Ismail; Khakam Ma'ruf; Rizal Justian S; Sudewo, Arizky Sudewo R; M.Zakky Al Ghifari; Cita insaniah M; Jauhari Ali (Prospect Publishing, 2024)
Innovation to improve environmental impact was conducted by PT Pertamina Patra Niaga Fuel Terminal Cikampek in accordance with the Life Cycle Assessment (LCA) analysis. One of them is related to reducing the load of water pollution by creating the Masaco Filter innovation (Water Hyacinth Cellulose Membrane). The innovation was created in line with the linkage of LCA and social innovation to answer a hotspot related to the impact of eutrophication. The Masaco filter applied to the Clean Water Management Installation or “Instalasi Pengelolaan Air Bersih” (IPAB) in the implementation of the Ngabedahkeun Walahar Program resulted in a reduction in Escherichia Coli levels from 100 CFU/100ml to 0 CFU/100ml and Total Coliform from 7 CFU/100ml to 0 CFU/100ml, Total Dissolve Solid which was previously 450 mg/L to 218 mg/LP, and dissolved manganese which was previously 30 mg/L to 0.01 mg/L so as to produce clean water hygiene and sanitation following the Minister of Health Regulation No. 2 of 2023 concerning Environmental Health Quality Standards.